Features of Body Composition in Centenarians with Coronary Artery Disease - S. V. Topolyanskaya; T. A. Eliseeva; N. A. Balyasnikova; O. N. Vakulenko; L. I. Dvoretski (Архивъ внутренней медицины)
Purpose. To investigate the body composition in patients over 90 years old (long-livers) with coronary artery disease (CAD), and analyzed the relationships between the fat and lean tissues, as well as bone mineral density. Material and Methods. A cross-sectional study of 200 patients over 90 years old (140 men and 160 women, mean age 92,4±2,3 года) who were hospitalized with a diagnosis of CAD was conducted. The body composition was analyzed by dual-energy X-ray absorptiometry (DXA). Results. Overweight or obesity were diagnosed in 139 (69.5%) patients. The musculoskeletal index remained within normal values in 145 (72.5%) patients and was below normal in 55 (27.5%) patients. Decrease of total BMD (T-score) below -2.5SD was detected in 81 (40,5%), and normal total T-score — in 60 (30.0%) patients. The smallest values of BMD were found in the ribs, the largest — in the spine and in lower extremities. A positive correlation was registered between body mass index and bone mineral density in all areas of the skeleton (p <0.0001). A significant positive correlation was found between BMD and the fat mass in all parts of the body, especially significant between BMD of the ribs and the trunk adipose tissue (r = 0.85; p <0.0001). A positive correlation has been established between the lean mass and BMD; the most significant between the BMD and the lean mass in the upper extremities (r = 0.69; p <0.0001). A negative correlation was found between the fat and lean mass; the most significant between lean and adipose tissue in the lower extremities (r = -0.46; p <0.0001). Conclusion. The study results indicate some features of body composition in long-livers. The proportion of overweight patients with normal indices of BMD and lean mass was relatively high. Significant relationships between the bone, adipose and lean tissues were confirmed.